Armed Resistance Movement and Guerrilla War in Estonia in 1941 - Noormets, Tiit (Genocidas ir rezistencija, 1997)
Partisan warfare as the highest stage of resistance in Estonia lasted only a few months in the summer of 1941, and the resistance movement began to take shape immediately after the occupation and the coup d’état on 21 June 1940. The first attempt was to create a legal opposition. In July 1940, before the election to the so–called people’s parliament, representatives of the former political parties and activists from the ethnic communities and academia organised the nomination of candidates of the ethnic forces to the parliament as a counterweight to the puppets of the new government. The cancellation of these candidates and even the abolition of formal democratic procedures already before the so–called election also put an end to all further attempts to organise legal opposition activities.